The Institutional Framework for National Food Security - Mostova Anastasiia D. (Problemi Ekonomiki, 2019)
The aim of the article is to study the institutional framework for ensuring national food security, systematize its main problems and develop strategic directions for its improvement. Based on the analysis of scientific papers, a definition of institutions and institutes for food security is proposed. It is proposed to define the main institutions that facilitate the functioning of the mechanism for ensuring national food security as institutions for: market mechanisms and market pricing; social standards and macroeconomic indicators; technical regulation, certification, safety and product quality; commodity and financial interventions, food reserve; national agrarian policy and measures to support producers; infrastructure of the agricultural and food market; methods and tools of strategic planning; food security information; legal support for food security. Food security institutions are reviewed and systematized in accordance with the strategic level, at which the mechanisms for shaping the food security strategy are concentrated, and the tactical level, at which the mechanisms for implementing, coordinating and monitoring food security strategies are provided. The article considers the specifics of key food security institutions that exercise control over and are responsible for the formation of strategic directions of the state agricultural policy on issues of price, technical regulation, public procurement, development of the agricultural sector of the economy and areas of support for domestic producers, rural development, food safety and quality, consumer protection, formation of food reserves, coordination of and control over the activities of government bodies in the field of food security in accordance with the current state of food markets. The main strategic priorities for improving the institutional support for food security in Ukraine are identified. The main directions for further research should be the development of measures and recommendations for improving the state agrarian policy.